PERAN PEMERINTAH DALAM MENJAGA STABILITAS HARGA BAHAN POKOK DI PASAR INDUK BONDOWOSO DALAM PERSPEKTIF EKONOMI ISLAM - Anwar, Zainul; Asmito, Asmito; Nisa, Khoirotun (Al-Idarah, 2025)
Price fluctuations of basic commodities are a classic issue in the regional economy that can affect people's purchasing power. This study aims to analyze the role of the Cooperatives, Industry, and Trade Office (Diskoperindag) of Bondowoso Regency in maintaining price stability of basic commodities in the market, as well as to identify supporting and inhibiting factors. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that Diskoperindag acts as a facilitator for the distribution of basic commodities, an operator of market operations, and a trade supervisor, but does not have the authority in price setting, taxes, and subsidies. In the perspective of Islamic economics, the role of Diskoperindag is similar to the function of al-ḥisbah, which is to ensure price affordability and fairness in market transactions. This research recommends strengthening the synergy between the Department of Cooperatives, Industry and Trade and central agencies to optimize price stabilization comprehensively and sustainably.